The strengths and weaknesses of Gramsci's cultural hegemony theory for the study of the discourse of mestizaje in Peru - Rodríguez Guillén, Carolina (2021)
This essay will assess the Gramscian account of cultural Hegemony for the study of the mestizaje discourse in Peru. In the first part of this essay the Gramsci account of cultural Hegemony will be addressed. Then, the second part will present what mestizaje discourse in Peru is and how can it be analyzed using Gramsci’s report of cultural Hegemony. Finally, the third part will use this both unpacked concepts to show the strengths and weaknesses of cultural Hegemony.